About the performance of the export of educational services and research activities of russian universities in modern conditions - O. N. Gutsynyuk; O. D. Poleshchuk; A. V. Ridiger (Informaciâ i Innovacii, 2024)
Purpose. Assessing the degree of influence of sanctions from “unfriendly countries” on the effectiveness of education export programs of Russian universities and on the research activities of organizations subordinate to the Russian Ministry of Education and Science.Results. The results of the analysis of the current regulatory and methodological framework in the field of international scientific and educational cooperation, the results of the analysis of departmental statistics.Conclusions. Subject to the functioning of the existing mechanisms of state financing of the higher education system, the activities of the industry (in relation to the area under study) remain little vulnerable to sanctions from “unfriendly countries”.